Back Cover: Chalcogen Bonding Catalysis of a Nitro‐Michael Reaction (Angew. Chem. Int. Ed. 47/2019). Issue 47 (6th November 2019) - Wonner, Patrick; Dreger, Alexander; Vogel, Lukas; Engelage, Elric; Huber, Stefan M.
Abstract : Chalcogen bonding is a noncovalent interaction between electrophilic chalcogen substituents and Lewis bases. In their Communication on page 16923 ff., S. M. Huber and co‐workers show that dicationic tellurium compounds can act as strong catalysts in a nitro‐Michael reaction. This is the first time that a nitro compound has been reported to be activated by halogen bonding or chalcogen bonding. The crucial role of chalcogen bonding was confirmed by comparison experiments.